Soft Tıssue Changes In Indıvıduals Wıth Dental Class I, Skeletal Class I, Class Iı, Class Iıı - Yaşar Göyenç; Ergin Şener; İrfan Karadede; Sedat Baran (Galenos Yayinevi, 1992)
The aim of this study is to evaluate the effect in soft tissue of compensation mechanism in the individuals with dental Class I, skeletal Class I, Class II, Class III. In this study, the individuals with excess overjet, anterior crossbite and over crowding have not been included. The study depends on lateral cephalometric films of 67 persons. 6 hard tissue, 9 soft tissue measurements have been made on films. The findings of Class I, Class II, Class III groups have been evaluated by statistical metods. As a result of, it was found that there were protrusion of lower incisors in Class II skeletal group, protrusion of upper incisors in Class III skeletal group, increase of thickness of lower lip in Class II skeletal group, increase of thickness of upper lip in Class III skeletal group. But, these variations are not adequate in correction of soft tissue profiL